The entrepreneurship of resource-based theory - Alvarez, Sharon A.; Busenitz, Lowell W. (Journal of Management, 2001)
This paper examines the relationship between resource-based theory and entrepreneurship and develops insights that advance the boundaries of resource-based theory and begin to address important questions in entrepreneurship. We extend the boundaries of resource-based theory to include the cognitive ability of individual entrepreneurs. Entrepreneurs have individual-specific resources that facilitate the recognition of new opportunities and the assembling of resources for the venture. By focusing on resources, from opportunity recognition to the ability to organize these resources into a firm and then to the creation of heterogeneous outputs through the firm that are superior to the market, we help identify issues that begin to address the distinctive domain of entrepreneurship.